2016
DOI: 10.1086/685856
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterning of Prey at Reproduction to Reduce Predation Risk: What Drives Dispersion from Groups?

Abstract: Group-living is a widespread behaviour thought to be an evolutionary adaptation for reducing predation risk. Many group-living species, however, spend a portion of their life cycle as dispersed individuals, suggesting that the costs and benefits of these opposing behaviours vary temporally. Here, we evaluated mechanistic hypotheses for explaining individual dispersion as a tactic for reducing predation risk at reproduction (i.e. birthing) in an otherwise group-living animal. Using simulation analyses parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…The effects of linear features on the movement of large terrestrial mammals are relatively well understood (Dyer et al, 2002; Whittington et al, 2004; Dickson et al, 2005; Latham et al, 2011; Whittington et al, 2011; McKenzie et al, 2012; Tremblay and Clair, 2009; DeMars et al, 2016; Dickie et al, 2017; Popp et al, 2018), but, here, we showed that anthropogenic linear features can also affect movement and space use of avian species during migration. Our approach was analytically nuanced, incorporating the affects of energy subsidies key to soaring movement into the the movement process.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The effects of linear features on the movement of large terrestrial mammals are relatively well understood (Dyer et al, 2002; Whittington et al, 2004; Dickson et al, 2005; Latham et al, 2011; Whittington et al, 2011; McKenzie et al, 2012; Tremblay and Clair, 2009; DeMars et al, 2016; Dickie et al, 2017; Popp et al, 2018), but, here, we showed that anthropogenic linear features can also affect movement and space use of avian species during migration. Our approach was analytically nuanced, incorporating the affects of energy subsidies key to soaring movement into the the movement process.…”
Section: Discussionmentioning
confidence: 55%
“…Some linear features have negative effects that are unidirectional in predator-prey interactions. Seismic lines, for example, increase a predator’s (wolf) access to prey (caribou), negatively affecting prey but imposing no additional risk or harm to the predator (McKenzie et al, 2012; DeMars et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of linear features on the movement of large terrestrial mammals are relatively well understood (DeMars et al, 2016;Dickie et al, 2019;Latham et al, 2011;McKenzie et al, 2012;Whittington et al, 2004); here we provide evidence that anthropogenic linear features also affect movement and space use of avian species during migration. Our approach was analytically nuanced, incorporating the effects of energy subsidies key to soaring movement into the availability kernel.…”
Section: Discussionmentioning
confidence: 67%
“…, Rettie and Messier , DeMars et al. ). We assumed that when a wolf encountered a caribou cow with her calf, only the calf was killed.…”
Section: Wolf–caribou Encounter Modelsmentioning
confidence: 99%
“…DeMars et al. () used a wolf detection distance for calves of 1 km; we used detection distances of 0.5 or 1 km. Note that it is possible that encounters between wolves and prey are missed because we only simulate wolf positions every five minutes.…”
Section: Wolf–caribou Encounter Modelsmentioning
confidence: 99%